2000 IEEE International Symposium on Circuits and Systems. Emerging Technologies for the 21st Century. Proceedings (IEEE Cat No
DOI: 10.1109/iscas.2000.856156
|View full text |Cite
|
Sign up to set email alerts
|

An efficient block-based interpreter for MPEG-4 structured audio

Abstract: The MPEG-4 Audio standard provides a toolset for Audio synthesis and Audio processing, i.e. Structured Audio (SA). SA permits to describe algorithms through its Structured Audio Orchestra Language (SAOL) programming language. Unlike some other languages of the same type, SAOL has a sample-by-sample execution structure, and this makes particularly important the overhead computation in case of an interpreted decoder implementation. This paper describes the design of an efficient virtual architecture able to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A more accurate description and details on such architecture solution can be found in (Zoia and Alberti, 2000).…”
Section: B the Virtual Ipmp System (Vis)mentioning
confidence: 99%
“…A more accurate description and details on such architecture solution can be found in (Zoia and Alberti, 2000).…”
Section: B the Virtual Ipmp System (Vis)mentioning
confidence: 99%
“…Complexity analysis and feedback analysis demonstrated that in most cases an efficient implementation of the SA decoder can be obtained by the design of an extended multimedia DSP, based on a vectorial instruction set [8].…”
Section: The Saint Architecturementioning
confidence: 99%